نبش القبر لإدخال ميتٍ على آخر دراسة فقهية تطبيقية على قطاع غزة: Exhumation of a Grave to Bury Another Deceased: An Applied Jurisprudential Study on the Gaza Strip - Abed Elfattah Eid, Noor Riyadh (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يتناول البحث مسألة واقعية، اضطر لها أهل غزة بكثرة أثناء حرب الإبادة التي تعرضوا لها، وهي مطروحة أيضًا في بعض المدن الإسلامية ذات الكثافة السكانية العالية، وهي مسألة نبش القبر لإدخال الميتِ حديثًا على آخر قد مات منذ مدة، وقد تعرض الباحث لهذه المسألة في الأحوال العادية، وفي حالة الضرورة، وكذلك في حالة بِلى الميت الأول أو بقاء أجزاء منه، وتعرَّض لمسألة نبش القبر لإلحاق أجزاء من الشهيد به، وذكر البحث حكم الدفن في الفساقي، وقد استخدم الباحث المنهج الوصفي، والاستقرائي، والتحليلي، وخلص لمجموعة من النتائج أهمها: حرمة إدخال ميت على آخر في الأحوال العادية، وإباحتها في أوقات الضرورة، وجواز دفن الأموات على شكل طبقات منفصلة في وقت الحاجة، وحرمة الدفن في الفساقي إلا إذا تخلصت الفَسقية من المحاذير الشرعية. ABSTRACT This research addresses a pressing issue frequently encountered by the people of Gaza during the genocide they faced lately, as well as in other densely populated Islamic cities. The issue pertains to the exhumation of a grave to bury a newly deceased person alongside one who had passed away earlier. The study examines this matter in three different situations, i.e. under normal circumstances, in cases of necessity, and when the remains of the first deceased have either decomposed or partially remained. It also explores the exhumation of graves to reunite parts of a martyr’s body with the rest. Additionally, the research discusses the legal ruling on burial in fassaqi (above-ground tombs). Employing descriptive, inductive, and analytical methodologies, the study arrives at several key findings. It affirms the prohibition of burying a deceased person over another in ordinary situations but acknowledges its permissibility in cases of necessity. It also supports the allowance of layered burials when required. Lastly, the study concludes that burial in fassaqi is generally prohibited unless the structure is free from any violations of Islamic legal principles.